AcERF2, an ethylene-responsive factor of Atriplex canescens, positively modulates osmotic and disease resistance in Arabidopsis thaliana. (September 2018) - Sun, Xinhua; Yu, Gang; Li, Jingtao; Liu, Jinliang; Wang, Xueliang; Zhu, Genglin; Zhang, Xianghui; Pan, Hongyu
Highlights: AcERF2 encodes an ethylene-responsive factor and is responsive to osmotic and low-temperature treatments. Overexpression of AcERF2 increases osmotic and disease resistance in Arabidopsis. AcERF2 positively manipulates the expression of abiotic and biotic stress-responsive genes. Overexpression of AcERF2 increases ABA responsiveness in Arabidopsis . VII ERFs from both monocot and dicot plants might utilize the similar regulatory mechanism in response to different stresses. Abstract: Ethylene-responsive factors (ERFs) comprise a large family of transcription factors in plants and play important roles in developmental processes and stress responses. Here, we characterized a novel AP2/ERF transcription factor, AcERF2, from the halophyte Atriplex canescens (four-wing saltbush, Chenopodiaceae ). AcERF2 was proved to be a transcriptional activator in yeast and localized to the nucleus upon transient expression in Nicotiana benthamiana, indicating its potential role as a transcription factor. Overexpression of AcERF2 driven by a CaMV35S promoter led to decreased accumulation of reactive oxygen species (ROS) and malondialdehyde (MDA), and increased antioxidant enzymatic activities, as well as rapid stomatal closure under osmotic treatment in Arabidopsis . Arabidopsis plants overexpressing AcERF2 were hypersensitive to abscisic acid (ABA) during germination, seedling establishment, and primary root elongation, and exhibited significant tolerance to osmotic stress. Furthermore, overexpression of AcERF2 induced transcript accumulation of plant defense-related genes ( PR1, PR2, PR5, ERF1 and ERF3 ) and increased Arabidopsis resistance to the bacterial pathogen Pseudomonas syringae pv. tomato DC3000 and the necrotrophic fungal pathogen Botrytis cinerea. These results suggest that AcERF2 may play a positive modulation role in response to osmotic stress and pathogen infection in plants.